Pengembangan Model Latihan Passing Sepak Bola Berbasis Sasaran Teman - Almayda, Ilham Danes (Jurnal Inovasi Olahraga, 2025)
This study was conducted to determine the effect of friend-based soccer passing practice on student players of Riau University's Sports Coaching Education. Considering the players in this team are very difficult during the match, as evidenced by the frequent loss of the ball, it is difficult to pass to friends. It all happened due to the lack of passing practice that the players had given the large size of the field. This research is an experimental research conducted with the aim of knowing whether or not there is a result of something that is done on the sample to be studied. The number of samples in this study amounted to 21 people. The exercises given were carried out for 18 meetings, 3 times a week using passing. The results showed that there was an improvement in the passing technique of soccer players from Riau University's Sports Coaching Education after being given passing training.